Severity Renal Function Detection through Critical Changes Glomerular Filtration Rate in Hemodialysis Patients - Martono Martono; Satino Satino (Universitas Airlangga, 2014)
Introductions: Hemodialysis is often interpreted incorrectly. People assume that the action is an action that will cure the treatment of hemodialysis patients with renal failure after hemodialysis. The purpose of this study was to determine the ability of critical changes in renal glomerular fi ltration rate in patients with hemodialysis nursing care.Methods: The design is quasi-experimental study carried out 2 times the observation that pre-test and post-test with a retrospective approach. The study population was all patients who underwent hemodialysis with a sample size of 33 respondents. Analysis of the research data using the paired t test.Results: The results of this study indicate that the glomerular fi ltration rate fi xing Hemodialysis towards better able to detect and prevent the severity of renal function as evidenced by the value of P = 0.031 for change 9.18.Conclusion: Hemodialysis fi x glomerular fi ltration rate towards better able to detect and prevent the severity of renal function with the ability to take into account the age and sex and weight stability. All the patients with chronic renal failure in the terminal stage are expected to follow and adhere to regular hemodialysis program with regard stabilization weight, age, and sex in order to avoid the severity of kidney function worse.